A Single-Material Logical Junction Based on 2D Crystal PdS2 - Ghorbani-Asl, Mahdi; Kuc, Agnieszka; Miro, Pere; Heine, Thomas (Advanced Materials, 2016)
A single-material logical junction with negligible contact resistance is designed by exploiting quantum confinement effects in 1T PdS2. The metallic bilayer serves as electrodes for the semiconducting channel monolayer, avoiding contact resistance. Heat dissipation is then governed by tunnel loss, which becomes negligible at channel lengths larger than 2.45 nm. This value marks the integration limit for a conventional 2D transistor.
CRIS-Team Scopus Importer:2023-03-20
Keywords: density functional theory; PdS; single material transistors; tunnel diodes